Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kepuasan Kerja di Kantor Unit Penyelenggara Pelabuhan Kelas III Kolaka - Hendrik Hendrik; Agus Zul Bay; Muh. Sri Bintang Lakay (Institut Nalanda, 2023)
This research aims to determine: (1) The influence of leadership on job satisfaction at the Kolaka Class III Port Management Unit Office. (2) The Influence of the Work Environment on Job Satisfaction at the Class III Kolaka Port Organizing Unit Office. This research is an exploratory research model with a quantitative method approach. Data collection in this research used observation, documentation and distribution of questionnaires. The population of this research is all employees of the Kolaka Class III Port Organizing Unit Office. Meanwhile, the sample for this research was 57 people using census techniques, namely researchers could examine all elements of the population. Research instrument testing uses validity and reliability tests with SPSS 22. The data analysis technique used in this research is measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the results of this research, it is known that there is a positive and significant influence between the Leadership variable on Job Satisfaction at the Class III Kolaka Port Organizing Unit Office as shown by the p-value of 0.000. Meanwhile, the Work Environment variable on Job Satisfaction at the Class III Kolaka Port Organizing Unit Office is shown by the p-value of 0.009.